Pembuatan pakan alami untuk pengembangan kepiting cangkang lunak di Desa Pulau Cawan Kecamatan Mandah kabupaten Indragiri Hilir - T. Ersti Yulika Sari; Usman Usman; Nur Asiah (Unri Conference Series: Community Engagement, 2020)
Mud crabs are mangrove crabs that are cultivated and harvested when molting so that their shells become soft and easy to consume. The purpose of this activity is to increase people's income in Desa Pulau Cawan, Kecamatan Mandah, Kabupaten Indragiri Hilir, through soft shell crab cultivation by introducing environmentally friendly cultivation techniques, but it can produce added value in terms of improving the family's economy through soft-shell crab cultivation, one of which is training in making natural feed. This is based on information from farmers who have never received training on feed manufacturing. Through the foster village program, knowledge and technology are given about techniques for making natural feed from lime water and spinach extract as a substitute for vitamalt which is quite expensive. The methods used in the Community activities of the foster Village are lectures, discussions and direct practice with POKDAKAN, starting with the preparation of spinach extract, trash fish, lime water, mixing and drying. The results of the evaluation of the counseling participants showed that 24 participants had never known about making natural feed from lime water and spinach extract as soka crab feed. After participating in this training activity there was an increase of 86.96% in knowledge about how to make natural feed. The partner's assessment of the implementation of this activity is 52.17% strongly agree that this natural feed can be made independently; 52.17% strongly agree that giving lime water and spinach extract to the artificial feed mixture of trash fish has an effect on the acceleration of the molting process in crabs and does not affect the survival of crabs; 60.87% strongly agreed that it could be an alternative livelihood; strongly agree that the molting process in soft-shell crab cultivation is the same as when the crabs are given a vitamolt, which is 20 days.